Regional oxidative stress in encephalon of female mice with polyphenolic exposure from tea extracts in oral overweight plant-based treatment - Miranda, Agustín Ramiro (2017)
Polyphenols provide by diet may act as antioxidant in the Central Nervous Systemand exert a protective effect on metabolic diseases. The aim of this study was toestablish tea extract effects on oxidative status and murine overweight in accordancewith polyphenolic availability in different encephalic regions. Methods: Balb/cmice (female, n>3) with overweight received for 15 days 100 mg/Kg/d of extractfrom Lantana grisebachii, Aspidosperma quebracho-blanco, or Ilex paraguariensisextracts and control group (received water without extract). Body weight gain wasrecorded regularly. Polyphenols, hydroperoxides (HP), lipid peroxides (LP), andsuperoxide anion (SO) were measured in brain (telencephalon and diencephalon),midbrain, brainstem and cerebellum. Results were compared by ANOVA followedby the Tukey test (P<0.05). Results: A. quebracho-blanco-based treatment decreasedweight gain and increased polyphenols in brainstem (p<0.02), although it concomitantly increased SO and LP in this region (p=0.0029 and p=0.0280, respectively).L. grisebachii-based treatment reduced oxidative markers differentially ineach region (p<0.05). I. paraguariensis-based treatment oxidized midbrain and cerebellum,although it was antioxidant in the brainstem (p<0.05). All treatments were antioxidant in telencephalon (p=0.0029). Conclusions: The A. quebracho-blanco extract was active on overweight and increased polyphenols in brainstem, with safe functional derivatives being required to avoid oxidative stress. Other extracts affected oxidative status in a region-dependent manner.